PERAN PERPUSTAKAAN UMUM DALAM MENINGKATKAN MINAT BACA DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI BALI - Adi Purnama, I Gst Ngr Nyoman; Haryanti, Ni Putu Premierita; Kastawa, Made (Jurnal Ilmiah D3 Perpustakaan, 2019)
ABSTRACT The purpose of this study is to find out the role of public libraries in increasing reading interest in the Bali Provincial Archives and Library Service in 2019 by using quantitative descriptive research methods. The data are through questionnaires. Total population is 1,697 users and the number of samples is 94 users. The research used sampling method as the sampling technique. The results of this research indicate that the reason for visiting the Bali Provincial Archives and Library Service is to increase knowledge, this is related to collections in the library that are adequate and relevant according to user needs. In addition, the information contained in the library helps users to be more active in reading. The conclusion of this study is that public libraries have a very important role in increasing reading interest. Keywords: library role, reading interest, collection